1990
DOI: 10.1016/s0022-5347(17)40016-4
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ureteropyeloscopy in the Diagnosis of Benign Essential Hematuria

Abstract: Benign essential hematuria is an uncommon syndrome that constitutes a dilemma in diagnosis for the urologist. We studied 32 patients with flexible ureteropyeloscopy. Previous studies included renal arteriography, computerized tomography, ultrasound and urinary cytology. The entire intrarenal collecting system was inspected in 28 of the 32 patients and discrete lesions were found in 16. The most common finding was a hemangioma on a renal papilla in 11 patients. A discrete lesion was treated in 12 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 14 publications
1
40
0
3
Order By: Relevance
“…Similar cases of non-specific pyelitis have been described by var ious authors, regardless of the approach used, even in the case of a pure retrograde approach (table 2), making it very unlikely for them to be iatrogenic. Their responsibili ty for the bleeding has been questioned by some authors because of the recurrence of haematuria after treatment, with no success in 4 patients treated with flexible ureteroscopic electrocoagulation in the series of Bagley and All en [3]. In contrast, our data suggest a direct responsibility of the lesions for the bleeding, as these lesions are associat ed with a good prognosis provided they are treated with a percutaneous approach (table 1).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Similar cases of non-specific pyelitis have been described by var ious authors, regardless of the approach used, even in the case of a pure retrograde approach (table 2), making it very unlikely for them to be iatrogenic. Their responsibili ty for the bleeding has been questioned by some authors because of the recurrence of haematuria after treatment, with no success in 4 patients treated with flexible ureteroscopic electrocoagulation in the series of Bagley and All en [3]. In contrast, our data suggest a direct responsibility of the lesions for the bleeding, as these lesions are associat ed with a good prognosis provided they are treated with a percutaneous approach (table 1).…”
Section: Discussionmentioning
confidence: 52%
“…They represent up to 25% of the lesions described in the cases studied (12/47; table 2). On the left side, these lesions may sometimes correspond to the endoscopic appearance of compression of the renal vein by the superior mesenteric artery ['nutcracker' pheWhen no real abnormality can be detected, some authors have suggested that venous caliceal communica tions may be responsible for unilateral haematuria [3], According to these authors, the raised intraluminal pres sure or inflammation induced by the endoscopic explora tion may be sufficient to occlude these venous abnormali ties and haematuria generally resolves after exploration without any associated therapeutic procedure [3]. How ever, even according to the same authors, this entity remains highly speculative, and the failure to detect small lesions, such as small haemangiomas, small excretory tumours or stones probably also accounts for part of the 17% (9/54) of normal examinations reported in the litera ture (table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fue preciso que algunos cirujanos se especializaran en la solución de entidades que requerían unas habili-dades específicas, que iban desde los clásicos sondajes a la propia endoscopia 76 , para que mejoraran las estrategias de hemostasia quirúr-gica casi inexistentes antes de la segregación. La urología como especialidad data de 1890 77 (mucho antes que la mayoría de apartados de la cirugía, aunque posterior a la oftalmología y la otorrinolaringología).…”
Section: Figura 4 Los Picados Pintura Atribuída a F De Goya Que Reunclassified